The merger of historically disadvantaged tertiary institutions in South Africa: A case study of the University of Limpopo - Dinkwanyane Kgalema Mohuba; Krishna Govender; Tahir Nisar (Cogent Business & Management, 2016)
Since the merger, few attempts have been made to interrogate the role of leadership on the operational stability of the new university. By employing a qualitative approach, this study allowed the participants to construct an accurate and, in-depth account of what really transpired during and after the merger. A case study design was used to focus intensely on the leadership challenges bedeviling the merger, using descriptive themes and qualifying vocabulary. Ten Project Steering Committee members of the merged institution were purposively selected to participate in the study. It was ascertained that most of the merger challenges related to poor communication, lack of stakeholder convergence, absence of buy-in from influential constituencies, lack of coherent strategies to deal with change and a lack of trust among the key drivers of the merger. It is recommended that government needs to ensure that future university mergers are stakeholder, rather than politically driven.
Keywords: 650